Investigating the genetic variability of 12 Vietnamese rice accessions (Oryza sativa L.) in response to phosphorus deficiency - Mai, Nga T P; Ngan Nguyen, Huyen; Hiep Nguyen, Van; Linh Duong, Viet; Nguyen, Phuong; Chung Mai, Duc; Lebrun, Michel; Mai To, Huong Thi (Vietnam Journal of Biotechnology, 2020)
Phosphate is the second major factor limiting on crop productivity and leads to various physiological disorders that would consequently affect plant development. In response to phosphate starvation, plants have to improve their root systems for efficiently acquired phosphate. In Vietnam, rice is one of the most important agricultural crops in which 60% of the rain-fed lowland rice is cultured on soil types, which are low in phosphorus or phosphate fixing. This fact along with the scenario in which phosphate resources are running out in fast pace, highly provoked an indispensible need for developing new rice varieties with high productivity under low phosphate condition. An emerging approach in order to accomplish this goal is through genetic improvement of local rice resources. Taking advantage of that, in this study, out of 182 sequenced Vietnamese rice accessions, 12 representatives from 3 distinguishing rice groups: Indica, Japonica and admix Indica subgroup were chosen. The variation in number of crown root, root length, shoot length, root mass, shoot mass, chlorophyll content and root anatomy were examined as parameters to analyze the effect of phosphorus deficiency (1 µM) compare to full phosphate medium (300 µM). The minimum number of plantlets used for each condition was 15. Each genotype was grown in Yoshida hydroponic medium (changed every 4 days, harvesting was made after 14 days). The experimental results showed a remarkable variation of different rice accessions in response to phosphate deficiency. The starvation of phosphate significantly affected almost all examined traits in which several accessions such as G38, G93, G165, G223, G62 accessions were potential hypersensitive and G11, G177 accessions were potential tolerant to P deficiency. These results are interesting and encouraging to further research for screening our Vietnamese rice collection in order to identify the set of potential genes responsible for tolerance in phosphorus starvation condition.